Acute kidney disease and renal recovery: consensus report of the Acute Disease Quality Initiative (ADQI) 16 Workgroup - Chawla, Lakhmir S.; Bellomo, Rinaldo; Bihorac, Azra; Goldstein, Stuart L.; Siew, Edward D.; Bagshaw, Sean M.; Bittleman, David; Cruz, Dinna; Endre, Zoltan; Fitzgerald, Robert L.; Forni, Lui; Kane-Gill, Sandra L.; et al. (Nature reviews. Nephrology, 2017)
Acute kidney injury (AKI) and chronic kidney disease are increasingly recognized as interconnected entities and the term acute kidney disease (AKD) has been proposed to define ongoing pathophysiologic processes following an episode of AKI. In this Consensus statement, the Acute Disease Quality Initiative 16 Workgroup propose definitions and staging criteria for AKD, and strategies for the management of affected patients. They also make recommendations for areas of future research with the aims of improving understanding of the underlying processes and improving outcomes. Consensus definitions have been reached for both acute kidney injury (AKI) and chronic kidney disease (CKD) and these definitions are now routinely used in research and clinical practice. The KDIGO guideline defines AKI as an abrupt decrease in kidney function occurring over 7 days or less, whereas CKD is defined by the persistence of kidney disease for a period of >90 days. AKI and CKD are increasingly recognized as related entities and in some instances probably represent a continuum of the disease process. For patients in whom pathophysiologic processes are ongoing, the term acute kidney disease (AKD) has been proposed to define the course of disease after AKI; however, definitions of AKD and strategies for the management of patients with AKD are not currently available. In this consensus statement, the Acute Disease Quality Initiative (ADQI) proposes definitions, staging criteria for AKD, and strategies for the management of affected patients. We also make recommendations for areas of future research, which aim to improve understanding of the underlying processes and improve outcomes for patients with AKD.